‘FOUR LEGS GOOD, TWO LEGS BETTER’: THE CHANGE OF UTOPIA TO DYSTOPIA IN GEORGE ORWELL’S ANIMAL FARM - Hasan, Mariwan; Aziz, Akar; Mawlood, Yahya (CALL, 2023)
This research is an analysis of the allegorical plot of Animal Farm and its clever usage of anthropomorphism in the change from a peaceful farm to a tyrannical one. This paper indicates the major features of the change from a utopian farm to a dystopian one, such as the perpetually increasing amount of labour that each animal has to undertake, the obvious decrease of ration which the pigs use for trading otherwise, the disturbing intervention into animals' personal freedom and thought by the totalitarian pigs and many more accounts that further establish such change. The aim of this was to shed light on those distinct paths that may lead any society towards dystopia, lest any community may have already begun going down such paths, to alert them and reverberate the sounding alarm. At the beginning, this research dealt with an introduction to the background of the time and literary movement that was present during the process of writing Animal Farm, namely the rise of the Stalinisit regime, and the surge of Utopian/Dystopian novels. The second chapter studies previous research written on the same topic as this one, the early events in Animal Farm and their effect on shaping the farm, and the significance of freedom within the farm. The third chapter consists of demonstrating the fundamental changes that contributed to the decline of the farm into its eventual dystopian nature, and a conclusion on the matter. The paper uses a textual and historical approaches in analyzing the texts of the novella.  Keywords: utopia, dystopia, orwell, labour, liberty, tyranny, commandment, censorship